Expansão e distribuição da educação superior em enfermagem no Brasil: desafios e perspectivas - SOARES, Fabiana Alves (2021)
Introduction: Over the years, there has been an intense expansion of undergraduate nursing courses and vacancies in nursing schools in the country, especially in the private sector. Objective: To analyze the expansion and distribution of higher education in Nursing in Brazil, from 1890 to 2019, according to the administrative category of the public or private educational institution. Methods: This is a cross- sectional study that used secondary data available online via the e-MEC portal. The data is related to 1,244 courses and 190,610 vacancies for the undergraduate Nursing courses in the face-to-face modality, which began operating between 1890 (year of creation of the first nursing school) until June 2019, the data collection period. Comparisons were made in the distribution of nursing courses and vacancies, according to the variables related to the institutions offering the course and geographic location. I was also considered if the courses were offered in the public or private sector. The rates of public, private, and total vacancies per 10,000 inhabitants were estimated for the Federative Units and macro-regions of Brazil. Also, the private/public ratio of the number of vacancies was calculated, and statistical differences were verified utilizing chi-square tests (α=5%). Results: Over 129 years, higher education in Nursing has become predominantly private and with a heterogeneous distribution of courses and vacancies across the country. Between 1997 and 2010, an intense expansion process was instituted, opening new courses and vacancies in all regions of the country, especially in the private sector. Thus, in 2019, there was a predominance of private courses (85.9%) and private vacancies (93.6%) for Nursing. Respectively, this offer of courses and private places for graduation was concentrated in large urban centers (56.0%; 67.1%) (p-value<0.05), in the Southeast Region (40.8%; 45.8%), and in the richest states: São Paulo (19.7%; 26.1%), Minas Gerais (12.5%; 9.1%) and Rio de Janeiro (9.0%; 10.2%). While courses (14.1%) and vacancies (6,4%) under public management did not follow this increase and were more frequent in the Northeast (36.6%; 32.2%) and interior of the states (57.7%; 53.8%) (p-value<0.05). Unequal vacancy rates/10,000 inhabitants were observed between the states and regions of the country, in which the North and South regions had the lowest density per vacancy per 10,000 inhabitants; in contrast, the Midwest, Southeast and Northeast regions had the highest. Conclusion: The temporal trajectory of expansion and distribution of courses and vacancies in Nursing education from the first course to 2019 was analyzed, according to the public or private nature of the institutions, showing the strong privatization movement of higher education in Nursing in Brazil, especially in the richer and more populated localities. The results contribute to reflections and criticisms about the trend of expansion of Nursing education in the country. The inequitable scenario of distribution of courses and vacancies reflects the rapid and disorderly way this expansion occurred, indicating the need to regulate the opening of new courses and vacancies. Although the number of courses and vacancies in nursing education has increased, they have not benefited the different locations of the country homogeneously.